A New Fixation Technique for French-Door Cervical Laminoplasty: Surgical Results With a Minimum Follow-up of 6 Years. Issue 4 (May 2017) - Harshavardhana, Nanjundappa S.; Dabke, Harshad V.; Mehdian, Hossein
Abstract : Design: A case series of 5 patients with multilevel cervical myelopathy treated by French-door cervical laminoplasty (FDCL) and use of unicortical iliac crest graft as spacer fixed with titanium miniplates and screws is described. Objective: To report a minimum of 6-year follow-up results of our new plate-screw fixation technique for FDCL. Summary of Background Data: Hardware-assisted laminoplasty has the potential advantage of preventing restenosis by holding the laminar door "open" while healing progresses and also prevents spacer dislodgement. The use of titanium miniplates as internal fixation device for FDCL by our novel technique has not been reported. Methods: Five patients suffering from multilevel cervical myelopathy harboring constitutionally narrow cervical canal (3) and multilevel cervical spondylotic myelopathy (2) who underwent 2–3 level FDCL and followed up prospectively for 6 years is presented. Modified Kurokawa and colleague's technique of FDCL was performed and autologous iliac crest bone graft was interposed between the sagittaly split spinous processes. A 12- to 15-hole titanium miniplate was contoured into a trapezoidal shape to sit flush with the posterior elements. The plate was anchored to bone graft and posterior elements with screws and patients mobilized without any external orthosis. Results: The mean follow-up was 90.5 months. The mean improvement in Neck disability index at final follow-up was 35% and mean improvement in Visual analog scale was 4 points. Japanese orthopaedic association score improved from a mean of 10 to a mean of 14.8 postoperatively. The final outcome was good (3) and excellent (2) by Odom's criteria. All patients improved to Nurick's grade 0 or I and reported significant relief from their myelopathic symptoms and axial neck pain. There were no postoperative hardware-related complications or pseudoarthrosis. Conclusions: Titanium miniplates are excellent devices for stabilizing the interspinous spacers used in FDCL. They prevent cervical canal deformation, restenosis, spacer dislodgement and are durable, cost-effective in facilitating early mobilization at intermediate-term follow-up of 6 years.